(untitled) (Nexo Revista Científica, 2021)
This study was performed on the outcrops of lamprophyric lavas found in the north of Jirandeh and east of Lushan in the mountain of Alborz (north of Iran). These lavas has been placed discordantly on the middle Eocene lime..Petrographic observation indicates olivine phenocrysts, green-core alkaline clinopyroxenes, nepheline, abundant biotite, and apatites with flakes. and in the matrix it also contains biotite, olivine, clinopyroxene and plagioclase.The presence of carbonates, plagioclase and xenocrystals with rounded margins asserts the contamination with continental crust Petrologically, these rocks classify as alkaline lamprophyres of comptonite variety.These rocks can be subsumed under alkaline sodic categories at K2O/Na2O<1 ratio. The rare elements patterns in the rocks, normalized with the primitive mantle, causing partial negative Nb anomalies and showing no blades at the surface. It, therefore, can be indicative of the evidence for an intraplate magmatism with the different degree in the crustal contamination. Geochemistry states the first cause of asthenospheric flow can be occurred at La/Nb<1 and La/Ta 13 ratios, and the presence of garnet can be assumed at 1/8< (Tb/Yb) N ratio in the rocks origin area. In tectonic discrimination diagrams, these rocks fall in the range of intra-continental rift zones. Geochemical analyses indicate that these lamprophyres originate from partial (1%) melting of an OIB-like asthenospheric mantle source of lherzolite garnet nature.